Lung worms of wild boars in the western region of Tokyo, Japan - Morita, T.(Nippon Veterinary and Life Science Univ., Musashino, Tokyo (Japan)); Haruta, K; Shibata-Haruta, A; Kanda, E; Imai, S; Ike, K (Journal of Veterinary Medical Science, 2007)
Prevalence of lung worms belonging to the genus Metastrongylus was surveyed on 42 Japanese wild boars (Sus scrofa leucomystax) captured officially for wildlife damage control in the western parts of Tokyo, Japan from April 2000 to April 2001. The number of parasites was the highest in the caudal lung lobes. Four species, M. elongatus (ME), M. salmi (MS), M. asymmetricus (MA) and M. pudendotectus (MP), were identified. All the boars were infected with 2 or more species, and 64.3% of the boars had all 4 species. The composition of species, ME:MS:MA:MP=1.3:3.4:1.0:1.4, was drastically different from the previous reports. The peak of the average number of the parasites was observed in the period of January to March 2001 because of the increase of MS.